Ответы и объяснения

2012-04-16T05:34:08+00:00

(х+1)(х+2)(х+3)(х+4)=1680   (перемножим попарно 1 и 4 скобки и  2 и 3 скобки )

(х² + 5х + 4)(х² + 5х + 6) =1680   

 

       Делаем замену:  y = х² + 5х + 4

y( y + 2) =1680  

y² + 2y - 1680= 0

D = 4 + 4*1680 = 6724      √D = 82

y = (-2 + 82 )/ 2                 ∨                 y = (-2 - 82 )/ 2

y = 40                                ∨                 y =  -42

   Обратная замена:

х² + 5х + 4 = 40                   ∨                 х² + 5х + 4  =  -42

х² + 5х - 36  = 0                   ∨                 х² + 5х + 46  =  0

D = 25 + 4*36 = 169                ∨              D = 25 - 4*46 =  - 159 

√D =13                                                         решений нет

х₁  = (-5 + 13) /2             =>     х₁  =   4

х₂  = (-5 - 13) /2             =>     х₂  =   -9

 

Ответ:  -9 ; 4.